Does technology-based self-service (TBSS) help tourists to revisit destinations? Validation of extended theory of planned behavior - Eunjoo Kang; Sungjoon Yoon (Global Business & Finance Review (GBFR), 2024)
Purpose: TBSS is expanding and increasing in tourist destinations, but there are not sufficient previous studies that took a multilateral approach to explain why and how people are induced to use TBSS in tourism settings. This study aims to investigate the role of technology-based self-service (TBSS) offered at tourist attractions on the tourists' reuse intention. Design/methodology/approach: This study, based on judgmental sampling, used online survey method to collect data from 402 respondents who previously visited Jeju Island of South Korea for touring purpose. The study used SPSS statistical 22.0 package to conduct multiple regressions analysis to test research hypotheses. Findings: The result indicates that technology-based self-services (TBSS) traits (i.e., playfulness, usefulness, ease of use, and reliability) all significantly influence five components of ETPB (attitude, subjective norms, perceived behavioral control, prior knowledge, and technostress). The study tested the validity of ETPB against two alternative models to confirm its added explanatory power of the extended model. Research limitations/implications: This study survey selected only those who have previously experienced TBSS at tourist attractions in Jeju Island located in South Korea. Therefore, this geographically limited sample may be difficult to generalize the result of the study. Originality/value: The study result provides useful theoretical contribution to solidifying a theoretical accounting of the two new variables (prior knowledge and technostress) as an extension of Theory of Planned Behavior. In particular, the study adds to existing literature by proposing a new mod다 of predicting tourism behavior based on TBSS setting.
Keywords: 650; ETPB; TBSS; Attitude; Subjective Norm; Perceived Behavioral Control